Efek Perendaman Bahan Fissure Sealant Semen Ionomer Kaca Pada Minuman Berkarbonasi Terhadap Pelepasan Fluor (The Effects of Immersion Material Glass Ionomer Cement Fissure Sealant on Carbonated Drinks to The Release of Fluoride Ions) - Armada Eka Fredian; Dyah Setyorini; Niken Probosari (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Application fissure sealant with glass ionomer materials effectively prevent the occurrence of dental hard tissue damage. Release of fluoride from glass ionomer can remineralize tooth and make it more resistant to acid. Application of glass ionomer sealant can expect an prevent damage hard tooth tissue on people who consume carbonated drinks in excess. The purpose of this study to determine the effects of immersion material glass ionomer cement fissure sealant on carbonated drinks to the release of fluoride ions . This research is an experimental laboratory with research design the post test only control group design . Glass ionomer material FUJI VII apllied on the buccal premolar and soaked with intervals of 30,60,90, 120 minutes and 24 hours in carbonated drink 50 ml . New replacement soaking solution performed on each interval . Calculation performed on each fluorine soaking solution using a spectrophotometer. Final result were analyzed using Kolmogorov Smirnov and Levene's test, followed by test Two way annova to see the difference between the control and treatment groups and followed by Duncan test to assess the difference between treatments. The results showed that the release of fluoride that has been soaked in a solution of glass ionomer materials . Fluoride content was highest at the beginning of immersion ( 30 minutes ) of 1.43 ppm and decreased significantly ( p > 0.05 ) in the next soaking up the content contained in the lows at the end of immersion ( 24 hours ) of 1.28 ppm. Key word : Carbonated drinks, fissure sealants, glass ionomer, the release of fluoride